Salicylic acid determines differential senescence produced by two turnip mosaic virus strains involving reactive oxygen species and early transcriptomic changes - Manacorda, Carlos Augusto (2013)
Losses produced by virus diseases depend mostly on symptom severity. Turnip mosaic virus (TuMV) is one of the most damaging and widespread potyvirus infecting members of the family Brassicaceae, including Arabidopsis thaliana. We used JPN1 and UK1 TuMV strains to characterize viral infections regarding symptom development, senescence progression, antioxidant response, reactive oxygen species (ROS) accumulation, and transcriptional profiling. Both isolates, despite accumulating similar viral titers, induced different symptomatology and strong differences in oxidative status. Early differences in several senescenceassociated genes linked to the ORE1 and ORS1 regulatory networks as well as persistent divergence in key ROS production and scavenging systems of the plant were detected. However, at a later stage, both strains induced nutrient competition, indicating that senescence rates are influenced by different mechanisms upon viral infections. Analyses of ORE1 and ORS1 levels in infected Brassica juncea plants showed a similar pattern, suggesting a conserved differential response to both strains in Brassicaceae spp. Transcriptional analysis of the ORE1 and ORS1 regulons showed similarities between salicylic acid (SA) response and the early induction triggered by UK1, the most severe strain. By means of SA-defective NahG transgenic plants, we found that differential senescence progression and ROS accumulation between strains rely on an intact SA pathway.